What are the complications and complication rates of cosmetic Botox injections?. Issue 5 (May 2016) - Lomeli, Matthew; Mercado, Michael
Abstract : Evidence‐based answer : Complications from cosmetic Botox injections depend on the location of treatment; they include headache (2%‐17%), brow ptosis (3.1%), blepharoptosis (2.5%), muscle imbalance (6.9%), muscle bulge (5.9%), and bruising (9.2%‐25%). Complications may last from several hours (headache) up to 1 month (some nerve paralysis) (SOR: A, systematic review of RCTs and subsequent RCT). Treatment applied to the upper and periocular regions of the face have the highest complication rates (4%‐8%) (SOR: C, case series).